Landscapes and Potentialities of Nature Tourism of the Central Feature of Serra Maracaju, Mato Grosso Do Sul, Brazil - Lima, Bruno de Souza (2022)
Mato Grosso do Sul, a state located in the central-western region of Brazil, is known for its unique landscapes, evidenced in established tourist destinations such as the Pantanal and Bonito. However, it is understood that other landscapes can serve as a place for developing nature tourism. The Serra de Maracaju runs through the central strip of the state, offers relevant and diverse landscapes throughout its extension, and houses areas whose structural characteristics encompass levels of highly transcendent and varied visual quality. The study presented here refers to the central feature of the Serra de Maracaju, an area in which three levels of potentialities have been identified using a correlation matrix based on landscape components